Routing lookup algorithm based on parallel BP neural network - Xiao-bo XU; Kang-feng ZHENG; Dan LI; Yi-xian YANG; IUXin-xin N (Tongxin xuebao)
A new routing lookup algorithm based on Bloom-filter algorithm and parallel back-propagation neural networks (BFBP) was proposed.The algorithm could meet the challenges of routing lookup and just had to learn the network ID moreover,it was equally attractive for IPv6.The results show that compared to other routing lookup methods based on neural network,BFBP algorithm reduces the average number of items which neural network has to learn by 520 times,improves learning efficiency of neural networks,and creates favorable conditions for the application of neural network in the area of routing lookup.